ChemInform Abstract: Topological Morphology Conversion Towards SnO2/SiC Hollow Sphere Nanochains with Efficient Photocatalytic Hydrogen Evolution. Issue 13 (1st April 2014) - Zhou, Xunfu; Liu, Yingju; Li, Xin; Gao, Qiongzhi; Liu, Xiaotang; Fang, Yueping
Abstract SnO2@C core—shell nanochains are obtained from aqueous solutions of Na2SnO3 and D‐glucose (autoclave, 180 °C, 4 h).